Mathematical Modeling and Experimental Verification of Oil-Gas Spring. (September 2020) - Chen, Yijie; Zheng, Guanhui; Han, Xiaoling; Zhang, Xu; Xu, Mengyan
Abstract: A method for studying the flexural deformation of the damping valve when subjected to a local uniform load was proposed, according to the physical model of valve platevalve platevalve platevalve platevalve platevalve platevalve plate and the related theory of thin plate mechanics, the differential equation of the deformation potential energy of the valve plate was solved, and the analytical formula of the flexural deformation under the local uniform load was derived. Further, combining the analytic formula of flexural deformation of the valve plate, the analytic formula of the annular gap throttling and the actual gas state equation, the mathematical model of the indicator characteristic of the hydro-pneumatic spring was derived. Through programming simulation, the relationship between the elastic force of the system and the total output force with displacement were analysed, compared with the test data, the correctness of the mathematical model of the hydro-pneumatic spring was verified, and the theoretical basis was provided by analytical formula of valve plate deformation.